Yeast β‐Glucan Improves Insulin Sensitivity and Hepatic Lipid Metabolism in Mice Humanized with Obese Type 2 Diabetic Gut Microbiota. Issue 22 (1st October 2022) - Mitchelson, Kathleen A. J.; Tran, Tam T. T.; Dillon, Eugene T.; Vlckova, Klara; Harrison, Sabine M.; Ntemiri, Alexandra; Cunningham, Katie; Gibson, Irene; Finucane, Francis M.; O'Connor, Eibhlís M.; Roche, Helen M.; O'Toole, Paul W.
Abstract : Scope: Gut microbiota alterations are associated with obesity and type 2 diabetes. Yeast β‐glucans are potential modulators of the innate immune‐metabolic response, by impacting glucose, lipid, and cholesterol homeostasis. The study examines whether yeast β‐glucan interacts differentially with either an obese healthy or obese diabetic gut microbiome, to impact metabolic health through hepatic effects under high‐fat dietary challenge. Methods and results: Male C57BL/6J mice are pre‐inoculated with gut microbiota from obese healthy (OBH) or obese type 2 diabetic (OBD) subjects, in conjunction with a high‐fat diet (HFD) with/without yeast β‐glucan. OBD microbiome colonization adversely impacts metabolic health compared to OBH microbiome engraftment. OBD mice are more insulin resistant and display hepatic lipotoxicity compared to weight matched OBH mice. Yeast β‐glucan supplementation resolves this adverse metabolic phenotype, coincident with increasing the abundance of health‐related bacterial taxa. Hepatic proteomics demonstrates that OBD microbiome transplantation increases HFD‐induced hepatic mitochondrial dysfunction, disrupts oxidative phosphorylation, and reduces protein synthesis, which are partly reverted by yeast β‐glucan supplementation. Conclusions: Hepatic metabolism is adversely affected by OBD microbiome colonization with high‐fat feeding, but partially resolved by yeast β‐glucan. More targeted dietary interventions that encompass the interactions between diet, gut microbiota, and host metabolism may have greater treatment efficacy. Abstract : Gut microbiota dysbiosis is associated with obesity and type 2 diabetes. Human obese diabetic microbiome transplantation specifically augments high‐fat diet induced hepatic steatosis and insulin resistance beyond obesity alone, which was resolved by yeast β‐glucan supplementation. Reverting adverse metabolic phenotypes requires precision nutrition ‐ understanding the interactions between diet, gut microbiota, and host metabolism to improve dietary management efficacy.